2018
DOI: 10.1016/j.devcel.2018.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Matrix-Remodeling Strategies Distinguish Developmental from Neoplastic Mammary Epithelial Cell Invasion Programs

Abstract: SUMMARY Metastasizing breast carcinoma cells have been hypothesized to mobilize tissue-invasive activity by co-opting the proteolytic systems employed by normal mammary epithelial cells undergoing branching morphogenesis. However, the critical effectors underlying morphogenesis remain unidentified and their relationship to breast cancer invasion programs have yet to be established. Here we identify the membrane-anchored matrix metalloproteinase, Mmp14/MT1-MMP, but not the closely related proteinase, Mmp15/MT2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 52 publications
(108 reference statements)
1
55
0
Order By: Relevance
“…These tumors, which grow confined inside the mammary ducts, have been recently shown to display large strands of collectively moving cells associated with the transition from in situ to the invasive stage of the tumor development ( 16 ). Additionally, the breast neoplastic invasive switch requires the activity of matrix proteases for breaching out of the duct ( 17,18 ).…”
Section: Introductionmentioning
confidence: 99%
“…These tumors, which grow confined inside the mammary ducts, have been recently shown to display large strands of collectively moving cells associated with the transition from in situ to the invasive stage of the tumor development ( 16 ). Additionally, the breast neoplastic invasive switch requires the activity of matrix proteases for breaching out of the duct ( 17,18 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, patterning of collagen fibers in the mammary gland stroma regulates the orientation of TEBs during branching morphogenesis (Brownfield et al, 2013). Recent publications reported important role of fibroblasts in regulation of ECM composition, abundance and organization, and thereby in regulation of mammary epithelial branching morphogenesis (Feinberg et al, 2018;Hammer et al, 2017;Koledova et al, 2016;Morsing et al, 2016;Peuhu et al, 2017). We found that FGF signaling in fibroblasts regulates expression of several ECM genes, including collagens.…”
Section: Discussionmentioning
confidence: 63%
“…We show that ID4 suppresses collagen synthesis and deposition around TEBs, which may otherwise act as a physical barrier to impede invasion. In support of this idea, ectopic deposition of collagen by mammary epithelial cells induced by exogeneous TGF-β, or forced expression of recombinant type I collagen which is resistant to collagenase attack, causes ensheathment of TEBs by collagen, and retardation of ductal elongation (Feinberg, Zheng et al, 2018, Silberstein et al, 1990).…”
Section: Discussionmentioning
confidence: 96%